2021
DOI: 10.3390/rs13142649
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Limitations of Grasslands α-Diversity Prediction Using Fine-Scale Hyperspectral Imagery

Abstract: Plant biodiversity is an important feature of grassland ecosystems, as it is related to the provision of many ecosystem services crucial for the human economy and well-being. Given the importance of grasslands, research has been carried out in recent years on the potential to monitor them with novel remote sensing techniques. In this study, the optical diversity (also called spectral diversity) approach was adopted to check the potential of using high-resolution hyperspectral images to estimate α-diversity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 49 publications
4
29
3
1
Order By: Relevance
“…Our study did not find a relationship between parcel area and species richness. Concerning the species-spectral heterogeneity pathway, our findings are consistent with very recent studies that suggested a dependency of this relationship on the grassland ecosystems studied [42,56]. In fact, Imran and colleagues [42,56] described that, in more natural conditions as those occurring in mountain grasslands, the spectral heterogeneity pathway did not perform adequately.…”
Section: Discussion Spatial Pathways For the Monitoring Of Grassland Parcels Biodiversity In Mountainssupporting
confidence: 86%
See 3 more Smart Citations
“…Our study did not find a relationship between parcel area and species richness. Concerning the species-spectral heterogeneity pathway, our findings are consistent with very recent studies that suggested a dependency of this relationship on the grassland ecosystems studied [42,56]. In fact, Imran and colleagues [42,56] described that, in more natural conditions as those occurring in mountain grasslands, the spectral heterogeneity pathway did not perform adequately.…”
Section: Discussion Spatial Pathways For the Monitoring Of Grassland Parcels Biodiversity In Mountainssupporting
confidence: 86%
“…Concerning the species-spectral heterogeneity pathway, our findings are consistent with very recent studies that suggested a dependency of this relationship on the grassland ecosystems studied [42,56]. In fact, Imran and colleagues [42,56] described that, in more natural conditions as those occurring in mountain grasslands, the spectral heterogeneity pathway did not perform adequately. Although interesting, our limited sampling size and set of variables do not allows us to further elaborate in this regard.…”
Section: Discussion Spatial Pathways For the Monitoring Of Grassland Parcels Biodiversity In Mountainssupporting
confidence: 86%
See 2 more Smart Citations
“…Increases in cost-effectiveness may also be increased by automated flight paths over survey locations, for which unsupervised spectral reflectance data could be collected. Furthermore, while rapid advancements have been made on spectral diversity, previous studies have utilised high-resolution multi/hyperspectral sensors that are either immobile, high-cost, or both (Frye et al, 2021; Gholizadeh et al, 2019; Imran et al, 2021; Lopatin et al, 2017). The current complete monitoring system is available for purchase for < 10,000 USD, relative to >50,000 USD for many hyperspectral sensors.…”
Section: Discussionmentioning
confidence: 99%